Digital reading: genealogy of formation and prospects for its development in a digitalized society - Yu. P. Melentieva (Библиосфера)
The theme of digital reading is becoming ever more relevant with a growing understanding of the importance of reading for developing both an individual and society as a whole. The issue addressed in the article is connected with the recently evolved concept of “digital reading”. The article is aimed at understanding digital reading and its core modifications – static (reading from the screen of an electronic gadget), reading of hypertext, reading in polymedia culture, as well as understanding what makes digital reading different (ideologically, physiologically, technologically) from traditional forms of reading. The author examines its genealogy as it was formed in the context of the evolution of writing and the emergence of new media and information centered printed culture. As a result the author specifies her own definition of digital reading and comes to the conclusion that it is most actively employed in education, which is rapidly becoming digitalized. The author also emphasizes the special function of modern libraries (public libraries, children’ libraries, school and university libraries), which should play the role of the “competent adult” in helping the user to develop the digital reading competences.